Pengaruh Modal Kerja Terhadap Profitabilitas Perusahaan Food And Beverages - Putri, Putu Intan Gana; Sudiartha, Gede Merta (E-Jurnal Manajemen; Vol 4 No 2 (2015), 2015)
This research as a purpose  to determined the effects of working capital/current assets turnover on profitability. Turnovers of working capital/current assets include cash turnovers, inventory turnovers and accounts receivable turnovers. The financial statements of the food and beverages company used as secondary data in this study with the time period of 2008-2010. Multiple linear regression, T-test and F-test is used as method analysis. The conclusion of this study is the analysis of working capital/current assets turnover simultaneous effect on profitabilities, while partially affecting profitability and inventory turnovers only accounts receivable turnovers.
Keywords: perputaran kas, perputaran piutang, perputaran persediaan, profitabilitas